THE AUTHORITY OF JUDGES IN GOVERNING THE EXCLUSIONARY RULE IN INDONESIA’S CRIMINAL JUSTICE SYSTEM - Matius Evan Anggara; Prija Djatmika; Yuliati (CV. RADJA PUBLIKA, 2025)
The doctrine of criminal evidence, encapsulated in the maxim in criminalibus probationes debent esse luce clariores, establishes that the evidence presented in criminal proceedings should be as transparent as light. This requirement entails that evidence—both in its formal dimension and in its material substance—must be subject to rigorous testing concerning the legality and authenticity of its acquisition. Nevertheless, the evidentiary process frequently encounters problems in both formal and material respects. Judicial scrutiny of evidentiary quality and admissibility includes, among others, examining whether documentary evidence was obtained through unlawful means or produced under circumstances that undermine its validity. Employing a normative juridical research method, this study investigates the judicial application of the Exclusionary Rules of Evidence in Indonesia’s criminal justice system through statutory and conceptual approaches.